Improved Survival from Ovarian Cancer in Patients Treated in Phase III Trial Active Cancer Centres in the UK. Issue 12 (December 2016) - Khoja, L.; Nolan, K.; Mekki, R.; Milani, A.; Mescallado, N.; Ashcroft, L.; Hasan, J.; Edmondson, R.; Winter-Roach, B.; Kitchener, H.C.; Mould, T.; Hutson, R.; et al.
Abstract: Aims: Ovarian cancer is the principal cause of gynaecological cancer death in developed countries, yet overall survival in the UK has been reported as being inferior to that in some Western countries. As there is a range of survival across the UK we hypothesised that in major regional centres, outcomes are equivalent to the best internationally. Materials and methods: Data from patients treated in multicentre international and UK-based trials were obtained from three regional cancer centres in the UK; Manchester, University College London and Leeds (MUL). The median progression-free survival (PFS) and overall survival were calculated for each trial and compared with the published trial data. Normalised median survival values and the respective 95% confidence intervals (ratio of pooled MUL data to trial median survival) were calculated to allow inter-trial survival comparisons. This strategy then allowed a comparison of median survival across the UK, in three regional UK centres and in international centres. Results: The analysis showed that the trial-reported PFS was the same in the UK, in the MUL centres and in international centres for each of the trials included in the study. Overall survival was, however, 45% better in major regional centre-treated patients (95% confidence interval 9–73%) than the median overall survival reported in UK trials, whereas the median overall survival in MUL centres equated with that achieved in international centres. Conclusion: The data suggest that international survival statistics are achieved in UK regional cancer centres. Highlights: We studied ovarian cancer survival, after initial management in trials in large regional cancer centres. These patients achieved international survival statistics that exceeded the UK average. Recurrent ovarian cancer might be best managed in large regional cancer centres.